Echinococcosis of the right thigh - U. R. Zhamilov; Kh. A. Isokov; G. A. Zhumankulov (Вестник хирургии имени И.И. Грекова)
Human echinococcosis, being a severe parasitic disease that affects almost any organs and tissues of the human body, has been known since ancient times. Cystic echinococcosis is the most common form of echinococcosis. It is an endemic zoonosis caused by the larval stage (metacestode) of the tapeworm E. granulosus. The localization of echinococcal cysts in the human body can be varied. In some cases, only one organ is affected, in others – several. Cysts can be multiple or single. The most common sites of hydatid cysts are the liver (60–70 %) and lungs (20 %), less commonly the parasites affect the spleen, kidneys, brain, heart and other organs, including bones.During surgical treatment, various methods are used to achieve the best result for the patient, with or without drug therapy. The literature we have studied provides isolated data on rare forms of echinococcosis. A clinical case of surgical treatment of a patient with a very rare localization of echinococcosis in the muscles of the right thigh is presented.